Setenta e cinco anos de publicação de O ex-mágico (1947), de Murilo Rubião, e a instauração da ficção do insólito absurdo no Brasil - García, Flavio (2022)
Although, in reality, injustices aside, relegating certain authors and works to oblivion, critics usually recognize that, in 1855, with the publication of the short story anthology Noite na taverna, by Álvares de Azevedo, under the pseudonym of Job Stern, fantastic fiction was inaugurated in Brazil, it was only from the end of the first half of the 20th century, with Murilo Rubião, that the fantastic began to gain some visibility. The historian and literary critic Antonio Candido, commenting on the new Brazilian narrative that would emerge from the third decade of this century, observes that, “[t]he book of short stories O ex-magic (1947), […] .] the fiction of the unusual absurdity was established in Brazil" (Candido, 1987, p. 208). Of the fifteen stories that make up the book, only two completely disagree with what can be conceptualized as an unusual absurdity. The others correspond perfectly to the contemporary fantastic discourse, either through the procedure of acting, spatialization, temporalization or unusual fabulation, alone or in combination (Prada Oropeza, 2006).